Presentation of Antibacterial and Therapeutic Anti-inflammatory Potentials to Hydroxyapatite via Biomimetic With Azadirachta indica: An in vitro Anti-inflammatory Assessment in Contradiction of LPS-Induced Stress in RAW 264.7 Cells - Nagaraj, Anusuya; Samiappan, Suja (Frontiers in Microbiology, 2019)
In the present study, for the first time, biomimetization of hydroxyapatite (HA) with Azadirachta indica (AI) was proposed and established its antioxidant, antibacterial, and anti-inflammatory potential on lipopolysaccharide (LPS). The ethanolic extract of AI was found rich with phenolics and flavonoids, and determined their concentration as 8.98 ± 1.41 mg gallic acid equivalents/g and 5.46 ± 0.84 mg catechin equivalents/g, respectively. The HA was prepared by sol-gel method from calcium nitrate tetrahydrate and orthophosphoric acid, and successfully biomimetization was done with ethanolic extract of AI. The FTIR analysis settled that as-synthesized HA-AI composite was comprised of both HA and AI. The XRD pattern and Zeta potential revealed that HA-AI composite was crystalline and negative in charge (– 24.0 mV). The average-size distribution, shape, and size of HA-AI composite was determined as 238.90 d.nm, spherical, and 177 nm from size distribution, SEM, and HR-TEM analysis, respectively. The SEM-EDX concluded that HA-AI composite was comprised of elements of HA as well as AI. The HA-AI composite presented potential antioxidant activity and its EC50 values (dose required to inhibit about half of radicals) for ABTS and DPPH assays were determined as 115.72 ± 2.33 and 128.51 ± 1.04 µg/mL, respectively. The HA-AI composite shown potent antibacterial activity, and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) towards S. aureus (ATCC 700699) and E. coli (ATCC 10536) were correspondingly determined as 266.7 ± 28.87 and 600.0 ± 50.0 µg/mL, and 400.0 ± 86.6 and 816.7 ± 76.38 µg/mL. Most importantly, HA-AI composite presented the potential anti-inflammatory response towards lipopolysaccharide (LPS) in RAW 264.7 cells. The dose of 250 µg/mL of HA-AI composite was shown optimum protection against LPS induced stress (1 µg/mL) by scavenging oxidants and regulating mitochondrial membrane potential (MMP), inflammatory and apoptotic factors. Thus, study concluded that impartation of potential bifunctional features to HA from plant sources through biomimetic approach is much beneficial and could find potential application in dentistry and orthopedics.